Bifunctional Silver(I) Complex‐Catalyzed CO2 Conversion at Ambient Conditions: Synthesis of α‐Methylene Cyclic Carbonates and Derivatives. Issue 5 (15th December 2014) - Song, Qing‐Wen; Chen, Wei‐Qiang; Ma, Ran; Yu, Ao; Li, Qiu‐Yue; Chang, Yao; He, Liang‐Nian
Abstract The chemical conversion of CO2 at atmospheric pressure and room temperature remains a great challenge. The triphenylphosphine complex of silver(I) carbonate was proved to be a robust bifunctional catalyst for the carboxylative cyclization of propargylic alcohols and CO2 at ambient conditions leading to the formation of α‐methylene cyclic carbonates in excellent yields. The unprecedented performance of [(PPh3)2Ag]2CO3 is presumably attributed to the simultaneous activation of CO2 and propargylic alcohol. Moreover, the highly compatible basicity of the catalytic species allows propargylic alcohol to react with CO2 leading to key silver alkylcarbonate intermediates: the bulkier [(Ph3P)2AgI]+ effectively activates the carbon–carbon triple bond and enhances O‐nucleophilicity of the alkylcarbonic anion, thereby greatly promoting the intramolecular nucleophilic cyclization. Notably, this catalytic protocol also worked well for the reaction of propargylic alcohols, secondary amines, and CO2 (at atmospheric pressure) to afford β‐oxopropylcarbamates.